Incidence and Clinical Characteristics of and Risk Factors for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection Among Pregnant Individuals in the United States. (19th August 2021) - Dawood, Fatimah S; Varner, Michael; Tita, Alan; Newes-Adeyi, Gabriella; Gyamfi-Bannerman, Cynthia; Battarbee, Ashley; Bruno, Ann; Daugherty, Michael; Reichle, Lawrence; Vorwaller, Kelly; Vargas, Celibell; Parks, Mickey; et al.
Abstract: Background: Data about the risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among pregnant individuals are needed to inform infection-prevention guidance and counseling for this population. Methods: We prospectively followed a cohort of pregnant individuals during August 2020–March 2021 at 3 US sites. The 3 primary outcomes were incidence rates of any SARS-CoV-2 infection, symptomatic infection, and asymptomatic infection, during pregnancy during periods of SARS-CoV-2 circulation. Participants self-collected weekly midturbinate nasal swabs for SARS-CoV-2 reverse transcription–polymerase chain reaction testing, completed weekly illness symptom questionnaires, and submitted additional swabs with coronavirus disease 2019 (COVID-19)–like symptoms. An overall SARS-CoV-2 infection incidence rate weighted by population counts of women of reproductive age in each state was calculated. Results: Among 1098 pregnant individuals followed for a mean of 10 weeks, 9% (99/1098) had SARS-CoV-2 infections during the study. Population-weighted incidence rates of SARS-CoV-2 infection were 10.0 per 1000 (95% confidence interval, 5.7–14.3) person-weeks for any infection, 5.7 per 1000 (1.7–9.7) for symptomatic infections, and 3.5 per 1000 (0–7.1) for asymptomatic infections. Among 96 participants with SARS-CoV-2 infections and symptom data, the most common symptoms were nasal congestion (72%), cough (64%), headache (59%), and change in taste or smell (54%); 28% had measured or subjective fever. Median symptom duration was 10 (interquartile range, 6–16) days. Conclusions: Pregnant individuals in this study had a 1% risk of SARS-CoV-2 infection per week, underscoring the importance of COVID-19 vaccination and other prevention measures during pregnancy while SARS-CoV-2 is circulating in the community. Abstract : During August 2020–March 2021, the incidence rate of SARS-CoV-2 infection among pregnant individuals at 3 US sites was 10.0 per 1000, equating to a 1% risk of infection per week. The asymptomatic fraction of infection was 35%.